2017
DOI: 10.1111/1742-6723.12809
|View full text |Cite
|
Sign up to set email alerts
|

Effect of known history of heart disease on survival outcomes after out‐of‐hospital cardiac arrests

Abstract: Known heart disease independently predicted poorer post-OHCA survival. This study may provide information to guide future prospective studies specifically looking at family education for patients with heart disease and the effect on OHCA outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…Results from each of the individual studies are shown online supplementary table 1 (for survival to hospital discharge outcomes) and online supplementary table 2 (for neurological outcomes). There were 18 studies conducted in Europe,3 5 10 13 15 28–40 four in the USA,8 12 41 42 three in Asia,20 26 43 two multinational studies,11 14 one in Australia9 and one in Canada 44. The number of patients enrolled in each study varied from n=6330 to n=2 47 684 41.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Results from each of the individual studies are shown online supplementary table 1 (for survival to hospital discharge outcomes) and online supplementary table 2 (for neurological outcomes). There were 18 studies conducted in Europe,3 5 10 13 15 28–40 four in the USA,8 12 41 42 three in Asia,20 26 43 two multinational studies,11 14 one in Australia9 and one in Canada 44. The number of patients enrolled in each study varied from n=6330 to n=2 47 684 41.…”
Section: Resultsmentioning
confidence: 99%
“…Patient inclusion age varied between studies, with 19 studies restricted to adults (≥16 years),3 8 9 12 20 26 28 29 31 33 36–44 one10 restricted to 70 years or over, seven placing no age restrictions5 11 13 15 32 34 35 and two studies being unclear about age 14 30. Cohort recruitment points varied greatly also, with 15 studies using scene of arrest as the enrolment point,5 8–11 13 20 31–33 38–40 42 44 6 using emergency department (ED) admission12 15 26 35–37 and 8 using hospital admission 3 14 28–30 34 41 43. Cardiac arrest aetiology was identified as either cardiac or non-traumatic in 12 studies,5 8–12 20 26 31 33 36 41 while the remaining studies either placed no restriction or were unclear.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when this factor was associated with age and chronic health problems, the survival rate was low. 26 In the results of this study it was also found that the majority of the patients who survived cardiac arrest had a shockable rhythm, unlike those who did not (p <0,001 Another finding was with regard to the administration of defibrillation in the ambulance. It appeared that most of the patients survived the arrest, in contrast to the patients who did not receive defibrillation in the ambulance (p <0,001).…”
Section: Discussionmentioning
confidence: 52%